2012
DOI: 10.1159/000343818
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Pediatric to Adult Healthcare: Assessment of Specific Needs of Patients with Chronic Endocrine Conditions

Abstract: Background/Aim: Transition from pediatric to adult care is a challenging turning point. The aim was to evaluate the transition process and needs expressed by patients with chronic endocrine conditions at transition in order to ensure program optimization. Methods: Prospective assessment of the transition period was conducted through completion of standardized questionnaires given to targeted patients. Two types were created: (1) a general questionnaire (GQ) addressing universal aspects of transition, and (2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 42 publications
(22 reference statements)
2
25
0
1
Order By: Relevance
“…Indeed, it is suggested that transfer should be organized at the time of another change in the adolescent life, for example, the end of school (15). This age is close to what was observed in other studies of transitioning CO-GHD patients (5,11) and to the age considered as ideal by patients in an autoquestionnaire (16). In this study, age at transfer is independent from etiology, sex, or year of transfer.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, it is suggested that transfer should be organized at the time of another change in the adolescent life, for example, the end of school (15). This age is close to what was observed in other studies of transitioning CO-GHD patients (5,11) and to the age considered as ideal by patients in an autoquestionnaire (16). In this study, age at transfer is independent from etiology, sex, or year of transfer.…”
Section: Discussionsupporting
confidence: 82%
“…Transition of young adults from paediatric care to adult care is a well-recognized challenge for patients with chronic endocrine conditions 247,248 including CHH. 175 For patients with CHH, discontinuation of care and resulting gaps in treatment can have considerable health consequences.…”
Section: Transitional Care For Chhmentioning
confidence: 99%
“…The transition from pediatric to adult care is a challenge for patients with chronic endocrine conditions with different disorders having condition-specific needs (85). Too often the transition process is characterized by cracks and gaps in care as reported for patients with TS (86) and CHH (82).…”
Section: Transition Of Adolescents To Adult Carementioning
confidence: 99%